Penampilan Penyakit Bulai yang disebabkan spesies Peronosclerospora philippinensis pada Kombinasi Perlakuan Varietas dan Fungisida Bahan aktif Metalaksil - Pakki, Syahrir; Aminah, Aminah; Saenong, Sujak; Muis, Amran (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2019)
Maize Downy Mildew caused by pathogenic fungus of Peronosclerospora philippinensis is an important disease in centers of maize crops outside Java Island. Research on â€œThe Appearance ofÂ MaizeÂ Downy Mildew Caused by Pathogenic Peronosclerospora philippinensis in Combination Treatment of Resistant Varieties and Metalaxyl Fungicide â€ aimed to determine the effectiveness of a combination of fungicide treatment of active ingredients of metalaxyl with varieties that have resistance to Maize Downy Mildew which was caused by P.philippinensis species. This research was conducted at KP Bajeng (endemic area ofÂ Maize Downy Mildew of P. Philippinensis species), which was compiled in Separate Plot Design with 3 replications. The main plot contained 5 varieties of maize, namely: (1) Bima-3 Bantimurung, (2) Bima-20 URI, (3) Lagaligo, (4) Bima-15 Sayang, and (5) Anoman. On the other hand, the sub plot contained 5 levels of seeds treatment dose with Metalaxyl Fungicide Active Ingredient (0 g/kg, 2 g/kg, 3 g/kg, 5 g/kg, and 7 g/kg of maize seed). The results showed that the combination of resistant and susceptible varieties with Metalaxyl Active Ingredient at doses of 2g, 3g, 5g and 7g/kg of maize seed controlled the Maize Downy Mildew which was caused by the Peronosclerospora philippinensis species effectively. It was shown by the low reaction of Maize Downy Mildew infection, at the percentage of 0% -1,86%, respectively. Under the circumstances of susceptible varieties without Metalaxyl Active Ingredient treatment, the intensity of Maize Downy Mildew reached the percentage of 100%. The lower intensity was also followed by the production, cob length and weight of 1000 seeds that were higher than those of control treatment.